2009
DOI: 10.2106/jbjs.h.01819
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Results of Three Posterior Cruciate Ligament Reconstruction Techniques

Abstract: Despite its technical difficulty, the arthroscopic tibial inlay double-bundle technique is our preferred method of reconstruction of the posterior cruciate ligament because it stabilizes posterior tibial translation better than do the other two methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
79
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 30 publications
1
79
1
1
Order By: Relevance
“…Its applications include diagnosing acute and chronic injuries [1,21,30,32], comparing instability preoperatively and postoperatively [20,24,39,55], and monitoring stability in nonoperatively treated patients [17]. A variety of stress techniques have been described that assess ligament stability using an anteriorly, posteriorly, varus-, or valgus-directed force to the knee [10,14,17,28,29,37,40,41,43,45].…”
Section: Introductionmentioning
confidence: 99%
“…Its applications include diagnosing acute and chronic injuries [1,21,30,32], comparing instability preoperatively and postoperatively [20,24,39,55], and monitoring stability in nonoperatively treated patients [17]. A variety of stress techniques have been described that assess ligament stability using an anteriorly, posteriorly, varus-, or valgus-directed force to the knee [10,14,17,28,29,37,40,41,43,45].…”
Section: Introductionmentioning
confidence: 99%
“…The killer turn was associated with friction, graft stretch, and fatigue failure [4,[31][32][33]56]. Although some clinical studies have not found a difference between the transtibial and open inlay techniques [2,29], there is also a body of literature to suggest unsatisfactory results with residual laxity given the transtibial technique [10,21,25,53]. The tibial inlay PCL reconstruction technique was first introduced in 1995 to circumvent the killer turn of the conventional transtibial technique [3].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Sensitivity analyses Table 3 indicated that the double bundle technique was significantly superior in patients with PCL isolated injuries (n ¼ 244; P ¼ 0.001 for all studies; P < 0.001 for RCTs; Table 3). 9,20,[22][23][24]29 There were no significant between-group differences in knee stability at 30 (n ¼ 138) 9,21,26,27 or ROM (Table 4) (n ¼ 88). 20,21 Studies using the Lysholm test found no significant between-group difference in outcome (n ¼ 372; Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…20,21 Studies using the Lysholm test found no significant between-group difference in outcome (n ¼ 372; Figure 3). 9,[21][22][23][24][26][27][28][29] Those reporting the Tegner activity scale indicated significantly better outcomes after doublerather than single bundle reconstruction (n ¼ 247; OR À0.34, 95% CI À0.68, 0.00; Figure 4). 9,[21][22][23]26 The IKDC examination was reported in five studies (n ¼ 222) [20][21][22][23]28 with outcomes categorized as grade A or grades C/D (Table 4).…”
Section: Resultsmentioning
confidence: 99%